PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN APLIKASI EMAZE TENTANG MATERI EKOSISTEM UNTUK PESERTA DIDIK SMAN 1 LUHAK NAN DUO - Putri, Firma; Alberida, Heffi; Yogica, Relsas; Anggryani, Ria (Universitas Cokroaminoto Palopo, 2025)
The Emaze learning media is a presentation tool that can be accessed through a computer or smartphone connected to the internet for usage. The aim of this research is to produce an interactive learning media using the Emaze application on the ecosystem material for students in class X Fase E at SMAN 1 Luhak Nan Duo that is valid and practical. The research type used is development, commonly known as R&D (Research and Development). The research sample is the class X Fase E at SMAN 1 Luhak Nan Duo. The data from the research were analyzed using qualitative data analysis and quantitative data analysis. The research results indicate that students agree with the development of learning media using the Emaze application, and 0% of students strongly disagree with the development of learning media using the Emaze application.